Roles of Crustacean Female Sex Hormone 1a in a Protandric Simultaneous Hermaphrodite Shrimp - Liu, Fang; Shi, Wenyuan; Huang, Lin; Wang, Guizhong; Zhu, Zhihuang; Ye, Haihui (Frontiers in Marine Science, 2021)
Crustacean female sex hormone (CFSH) plays a pivotal role in the development of secondary sex characteristics in dioecious crustaceans. However, until now the knowledge concerning its functions in hermaphroditic species is scanty. Herein, we explored the function of CFSH (Lvit-CFSH1a) in the peppermint shrimp Lysmata vittata, a species characterized by a rare reproductive system of protandric simultaneous hermaphroditism (PSH). Lvit-CFSH1a cDNA was 1,220-bp in length with a 720-bp ORF encoded a polypeptide of 239-aa. RT-PCR showed that Lvit-CFSH1a was exclusively expressed in the eyestalk ganglion. For female physiology, it was found that Lvit-CFSH1a was indispensable for the development of female gonopores, but it might not involve vitellogenesis of the species. For male physiology, Lvit-CFSH1a suppressed Lvit-IAG2 expression in short-term silencing experiment and recombinant protein injection experiment, but did not affect male sexual differentiation in long-term silencing experiment. In addition, silencing the Lvit-CFSH1a gene impeded individual growth in L. vittata.